New advances in obtaining three-dimensional models from conical perspectives. (August 2016) - Conesa, J.; Mula, F.
Highlights: The algorithms proposed allow automatically obtaining models from the graphs representing a conical perspective. The system proposed does not need to know the faces defined in the model. The algorithms proposed allow expanding the reconstruction model through some oblique edges in the model. The methods have been implemented and simulated, obtaining a success rate of 100%. Abstract: In a previous work we presented algorithms which allow obtaining three-dimensional models from graphs which represent a projection in conical parallel perspectives and conical oblique perspectives of polyhedral models with normalon and quasi-normalon typology. In this paper the new advances that we have achieved in this field are presented, allowing increasing the set of models which can be reconstructed to other typologies different from the normalon and quasi-normalon ones. Moreover, we present a new technique which extends the previous work in order to be implemented to conical perspectives with three vanishing points, and the method proposed for the detection of the type of conical perspective represented by the graph, including the detection and subsequent reconstruction of graphs which represent a flat shape, has been improved. The results obtained on a total of 336 tests, with a success ratio of 100%, make the method a proposal to be considered for obtaining models from conical perspectives automatically.